MiR-181a Regulates Blood-Tumor Barrier Permeability by Targeting Krüppel-Like Factor 6. Issue 11 (November 2014) - Ma, Jun; Yao, Yilong; Wang, Ping; Liu, Yunhui; Zhao, Lini; Li, Zhen; Li, hiqing; Xue, Yixue
Blood-tumor barrier (BTB) constitutes an efficient organization of tight junctions that impairs the delivery of therapeutic drugs. However, the methods and molecular mechanisms underlying the BTB opening remain elusive. MicroRNAs (miRNAs) have recently emerged as key regulators of various biologic processes and therapeutic targets. In this study, we have identified microRNA-181a (miR-181a) as a critical miRNA in opening BTB. MicroRNA-181a expression was upregulated in glioma endothelial cells (GECs), which were obtained by coculturing endothelial cells (ECs) with glioma cells. Overexpression of miR-181a resulted in an impaired and permeability increased BTB, and meanwhile reduced the expression of zonula occluden (ZO)-1, occludin, and claudin-5. Kruppel-like factor 6 (KLF6), a transcription factor of the zinc-finger family, was downregulated in GECs. Mechanistic investigations defined it as a direct and functional downstream target of miR-181a, which was involved in the regulation of BTB permeability and the expression of ZO-1, occludin, and claudin-5. Furthermore, luciferase assays and chromatin immunoprecipitation assays showed that KLF6 upregulated the promoter activities and interacted with the promoters of ZO-1, occludin, and claudin-5 in GECs. Collectively, we showed the possibility that overexpression of miR-181a contributes to the increased permeability of BTB by targeting KLF6, thereby revealing potential therapeutic targets for the treatment of brain gliomas.